PENGARUH GAYA KEPEMIMPINAN TERHADAP PENINGKATAN DISIPLIN PEGAWAI PADA KANTOR CAMAT KECAMATAN GANDUS KOTA PALEMBANG - Anggun Badriyansyah Fahlevi (STIA SATYA NEGARA PALEMBANG, 2022)
Leadership in an organization has a fairly broad impact including employee behavior, leadership that is able to move employees is likely to improve employee performance. However, on the other hand, leadership that does not get support from employees is likely to work lazily because of a lack of sympathy for the leader. A good leader seeks to apply flexible discipline, so that his subordinates can carry out their duties and be disciplined based on employee awareness without coercion, but authoritarian leaders tend to impose their will on their subordinates, so that subordinate discipline is a discipline that does not originate from its own consciousness. The research method used is a quantitative method. Data was collected by means of observation, interviews, questionnaires, literature study. Data analysis was carried out by means of Multiple Regression Test.The results of the research and discussion show that leadership is able to influence employee discipline. The amount of influence given by charismatic leadership is 0.516, which means that if it is quadranted, the correlation result is multiplied by 100%. Then it is found that the influence of leadership style on improving employee discipline is 51.6%. While the rest (100-51.6=48.4%) are influenced by other variables. Keywords: Leadership, Employee Discipline